Governor's House, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A picture of a walkway leading to the Governor's House main building, now known as the President's House, starting at a fountain, tropical plants of the Botanical Gardens line the walkway and at the back of the building are the St. Ann's Hills. The postcard is addressed to Miss Jean Scheuble, Pittsburg, Pennsylvania, U.S.A. and bears the number 351.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Fountains--Trinidad and Tobago; Historical buildings--Trinidad and Tobago; President's House, The